Challenges and Adaptation Strategies of Madrasah, Islamic Schools, and Pesantren in Facing Global Competition - Tubagus Panambaian; Husnul Yaqin; Hamdan Hamdan; Hidayat Ma’ruf (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to identify the global challenges faced by Islamic educational institutions (madrasahs, Islamic schools and pesantren) in Indonesia and to analyse effective strategies for enhancing their competitiveness. The study employed a qualitative literature review method, analysing various academic journals, books, and official reports from the Ministry of Religious Affairs and the Central Statistics Agency over the past five years. The findings indicate that the main challenges include socio-cultural changes that threaten local Islamic values, fierce competition with state and international schools, and managerial and funding constraints. The study also found that successful adaptation strategies include the implementation of quality management, curriculum innovation integrating religious and general studies, the utilisation of digital technology, institutional collaboration, teacher competency development, international partnership programmes, and outcome-based evaluation. In conclusion, Islamic educational institutions must undergo holistic transformation without losing their essential identity in order to remain relevant and competitive on the global stage. This research provides a strategic framework for Islamic education leaders in facing global competition.